2018
DOI: 10.1159/000490418
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Attenuates Osteoarthritis via Upregulating AMP-Activated Protein Kinase/Proliferator-Activated Receptor-γ Coactivator-1 Signaling Pathway in Osteoarthritis Rats

Abstract: Background/Aims: Osteoarthritis is the most common degenerative joint disease and causes major pain and disability in adults. It has been reported that mitochondrial dysfunction in chondrocytes was associated with osteoarthritis. Puerarin has multiple effects including restoring mitochondrial function. In this study, the potential effects of puerarin on osteoarthritis and osteoarthritis associated mitochondrial dysfunctions were evaluated. Methods: Osteoarthritis rats were treated with puerarin and the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…The dogs were ranged by weight and randomly divided into control group (sham operation, n = 4) and model group (ACLT surgery, n = 12) to which the animal care personnel were blinded. The model group is divided into 3 subgroups (n = 4 in each group): OA group: untreated; celecoxib group: 200 mg/day celecoxib [32] (P zer Pharmaceutical, New York, USA) treated canine OA (positive control); Puerarin group: puerarin (Chengdu Mansite Biological Technology, Chengdu, China) 20 mg/kg/day to treat canine OA; The dosage of puerarin was determined according to previous studies [16,17] and according to FDA guidelines [45]. The Laboratory Animal Welfare and Ethics Committee of Northeast Agricultural University (#NEAU-2017-06-0384-12) approved the experimental design and animal surgery procedures in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dogs were ranged by weight and randomly divided into control group (sham operation, n = 4) and model group (ACLT surgery, n = 12) to which the animal care personnel were blinded. The model group is divided into 3 subgroups (n = 4 in each group): OA group: untreated; celecoxib group: 200 mg/day celecoxib [32] (P zer Pharmaceutical, New York, USA) treated canine OA (positive control); Puerarin group: puerarin (Chengdu Mansite Biological Technology, Chengdu, China) 20 mg/kg/day to treat canine OA; The dosage of puerarin was determined according to previous studies [16,17] and according to FDA guidelines [45]. The Laboratory Animal Welfare and Ethics Committee of Northeast Agricultural University (#NEAU-2017-06-0384-12) approved the experimental design and animal surgery procedures in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin in collagen matrix has the effect of increasing new bone formation locally and can be used for bone grafting or for bone induction [15]. Previous studies have shown that in rat and mouse OA models, puerarin can effectively inhibit in ammation and improve OA [16,17]. However, the effect of puerarin on canine OA has not been evaluated.…”
Section: Paragraphmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction in chondrocytes is associated with OA, and induces oxidative stress [88]. Puerarin [88] and quercetin [84] may attenuate mitochondrial dysfunction in OA rats. Subsequently, oxidative stress induces endoplasmic reticulum stress in OA, and quercetin may also repress this process by activating the sirtuin1/AMPK signaling pathway [21].…”
Section: The Effects Of Bioactive Components On Cartilage In Oamentioning
confidence: 99%
“…Resveratrol [ 61 ], tetramethylpyrazine [ 13 , 70 ], celastrol [ 54 ], isofraxidin [ 33 , 34 ], paeonol [ 56 ], shikonin [ 35 ], coptisine [ 44 ], piperine [ 45 ], butein [ 46 ], genistein [ 58 ], kaempferol [ 47 ], licochalcone A [ 36 ], honokiol [ 50 ], 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-d-glucoside [ 60 ], compound K [ 37 ], geniposide [ 31 ], emodin [ 38 ], and curcumin [ 65 ] may reverse the abnormal expression of these indexes. Mitochondrial dysfunction in chondrocytes is associated with OA, and induces oxidative stress [ 88 ]. Puerarin [ 88 ] and quercetin [ 84 ] may attenuate mitochondrial dysfunction in OA rats.…”
Section: The Anti-oa Activities Of Bioactive Components From Herbal Mmentioning
confidence: 99%